The arts of China - Sullivan, Michael 1916-2013; Vainker, S. J. (University of California Press, 2018)
Preface to Sixth Edition -- Afterthoughts -- Chronological Table of Dynasties and Modern Republics -- Reign Periods of the Ming and Qing Dynasties -- Before the Dawn of History -- The Early Bronze Age: Shang and Western Zhou -- Eastern Zhou and the Period of the Warring States -- The Qin and Han Dynasties -- The Three Kingdoms and the Six Dynasties -- The Sui and Tang Dynasties -- The Five Dynasties and the Song Dynasty -- The Yuan Dynasty -- The Ming Dynasty -- The Qing Dynasty -- The Twentieth Century and Beyond